MEANS OF PHYSICAL CULTURE THAT ENSURE THE STABILITY OF HUMAN PHYSICAL PERFORMANCE - Khatamov Zafarjon Nazirjonovich; Boltaboev Hamidullo Khabibulloevich; Akhmedov Mukhammadjon (Ta’lim innovatsiyasi va integratsiyasi, 2023)
There is a physiological classification of exercises in which all the diverse muscular activity is combined into separate groups of exercises based on physiological characteristics. The body's resistance to adverse factors depends on innate and acquired properties. It is very mobile and can be trained both by means of muscle loads and various external influences (temperature fluctuations, lack or excess of oxygen, carbon dioxide). It is noted, for example, that physical training by improving physiological mechanisms increases resistance to overheating, hypothermia, hypoxia, the action of certain toxic substances, reduces morbidity and increases efficiency.